Music - the Cultural Bridge. Essence, Contexts, References - Pijarowska, Aleksandra. Redakcja naukowa (Akademia Muzyczna im. Karola Lipińskiego we Wrocławiu, 2021)
Music - the Cultural Bridge. Essence, Contexts, References is a unique publication prepared within the Eastern Academic Artistic Platform project as a part of the International Academic Partnerships Programme announced by the National Agency for Academic Exchange. The aim of this project is to establish a partnershipbetween four countries that share elements of culture but have undergone different influences – Estonia, Georgia, Ukraine and Poland – for the purpose of developing mechanisms of collaboration in the field of academic and teaching work. This is implemented through the promotion of the national artistic output ofeach of the four countries, and the exchange of knowledge about innovative research methods. As part of the project, the publication is intended to create abridge uniting a unique musical sector encompassing four academies: Lviv National Music Academy n.a. Mykola Lysenko, Estonian Academy of Music and Theatre inTallinn, Vano Sarajishvili Tbilisi State Conservatoire and the Karol Lipiński Academy of Music in Wrocław. The book includes articles by outstanding scholars, representatives of the partner academies. The introductory paper on Wrocław-Based Composers and Polish Music Trends in the Second Half of the 20th Century and at the Beginning of the 21st Century by Anna Granat-Janki is followed by other studies divided into four thematic sections: Musical Heritage and Political Stigma, Folklore and Traditional Music, Musica hic et nunc, and Figures, Styles, Trends, Perspectives. The publication focuses on the artistic output, achievements and important figures that create the unique cultural idiom of each of the countries and at the same time help to build the long-lasting, recognisable cultural heritage shared by the four partners, and thus we believe it will inspire reflection on the identity, future and perspectives of Estonian, Georgian, Ukrainian and Polish culture.
Keywords: muzyka; kultura; muzyka estońska; muzyka gruzińska; muzyka polska; muzyka ukraińska; historia muzyki; muzyka ludowa; muzykoterapia; estonian music; georgian music; polish music; ukrainian music; history of music; folk music; music therapy